Validity and Reliability of the Spanish Version of the Technological Competency as Caring in Nursing Instrument - Daniel Andrés Rincón Álvarez (Universidad de Antioquia, 2017)
Objective. This work aimed to evaluate validity and reliability to measure the technological competency of Nursing in Colombia of the Spanish version of the Technological Competency as Caring in Nursing Instrument (TCCNI).